Beta-cell sensitivity to insulinotropic gut hormones is reduced after gastric bypass surgery. Issue 10 (16th February 2019) - Salehi, Marzieh; Gastaldelli, Amalia; D'Alessio, David A
Abstract : Objective: Postprandial hyperinsulinaemia after Roux-en Y gastric bypass (GB) has been attributed to rapid nutrient flux from the gut, and an enhanced incretin effect. However, it is unclear whether surgery changes islet cell responsiveness to regulatory factors. This study tested the hypothesis that β-cell sensitivity to glucagon like-peptide 1 (GLP-1) and glucose-dependent insulinotropic peptide (GIP) is attenuated after GB. Design: Ten non-diabetic subjects with GB, and 9 body mass index (BMI)-matched and age-matched non-surgical controls (CN) with normal glucose tolerance had blood glucose clamped at ~7.8 mM on three separate days. Stepwise incremental infusions of GLP-1 (15, 30, 60, 120 and 300 ng/LBkg/h), GIP (75, 150, 300, 600 and 1200 ng/LBkg/h) or saline were administered from 90 to 240 min and insulin secretion measured. Results: GB subjects had similar fasting glucose levels but lower fasting insulin compared with CN, likely due to increased insulin clearance. The average insulin secretion rates (ISRs) to 7.8 mM glucose were ~30% lower in GB relative to CN subjects. However, incretin-stimulated ISRs, adjusted for insulin sensitivity and glucose-stimulated insulin secretion, were even more attenuated in the GB subjects, by threefold to fourfold (AUCISR(90−240 min) during GLP-1 and GIP: 47±8 and 44±12 nmol in GB and 116±16 and 161±44 in CN; p<0.01). Conclusion: After GB, the sensitivity of insulin secretion to both glucose and incretins is diminished.